Síntese de biodiesel a partir do farelo de arroz via catálise enzimática - Pereira, José Evandro Saraiva (2013)
Technological advances that allow reducing the biodiesel production process costs practiced today, are needed to make it more competitive against fossil fuels costs. In this context, the present work studied two methods for the synthesis of biodiesel via enzymatic catalysis using rice bran and the crude oil extracted from it, through the biotransformation of oil in the rice bran and using the lipase found in raw material as biocatalyst. When it was used the molar ratios of methanol:oil 8:1 and hexane:methanol 12:1, 35°C, 180 rpm, 10.5% moisture, 25 g of rice bran for 24 h the reaction with the addition of methanol in two steps has been reached 5.7% conversion to methyl esters. This result demonstrated that the hydrophobic organic solvent with log P > 3 assisted enzymatic catalysis when compared polar solvent (acetronitrile/t-butanol/methanol). The pH adjustment of the medium with the addition of potassium methoxide (1% w/w KOH/oil) under the same reaction conditions increased in 2.2 times conversion to methyl esters (12.9%). The addition of higher concentrations of potassium methoxide (1.5 and 2% w/w) kept the pH ≈ 7, but had no effect on the conversion to methyl esters, unlike promoted a decrease to 10.7% and 7.1%, respectively. The enzymatic catalysis performed on the crude oil extracted from rice bran with molar ratios of methanol:oil 3:1 and hexane:methanol 3:1 using Porcine pancreatic lipase keeping constant the other reaction parameters, led to a 72.1% of conversion to methyl esters. This work showed that, under suitable conditions, the enzyme lipase is more protected from methanol toxicity, while it improves the solubility of the alcohol in the oil thereby promoting the synthesis of biodiesel from rice bran.